2016
DOI: 10.1038/ejhg.2016.136
|View full text |Cite
|
Sign up to set email alerts
|

Carriers with functional null mutations in LAMA3 have localized enamel abnormalities due to haploinsufficiency

Abstract: The hereditary blistering disease junctional epidermolysis bullosa (JEB) is always accompanied by structural enamel abnormalities of primary and secondary dentition, characterized as amelogenesis imperfecta. Autosomal recessive mutations in LAMA3, LAMB3 and LAMC2 encoding the heterotrimer laminin 332 (LM-332) are among the genes causing JEB. While examining pedigrees of JEB patients with LAMA3 mutations, we observed that heterozygous carriers of functional null mutations displayed subtle enamel pitting in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…8 , 9 , 10 , 11 Mutation or deletion of the LM332 α3 chain (LAMA3) can result in complete loss of LM332 in the basement membrane and affect HD formation, which eventually, can lead to junctional epidermolysis bullosa. 12 , 13 Taken together, those findings suggest that LAMA3 has a promising role in promoting LM332 synthesis and HD formation.…”
Section: Introductionmentioning
confidence: 79%
“…8 , 9 , 10 , 11 Mutation or deletion of the LM332 α3 chain (LAMA3) can result in complete loss of LM332 in the basement membrane and affect HD formation, which eventually, can lead to junctional epidermolysis bullosa. 12 , 13 Taken together, those findings suggest that LAMA3 has a promising role in promoting LM332 synthesis and HD formation.…”
Section: Introductionmentioning
confidence: 79%
“…Many recent studies have indicated that adhesion and extracellular matrix proteins contribute to the progression of a variety of solid tumors, including pancreatic cancer 20–22 . LM-332, which is encoded by LAMA3, LAMB3, and LAMC2, is related to tumor invasiveness in various types of malignant tumors 2325 . LAMB3 is a potential biomarker of cancer invasion and metastasis that is involved in the focal adhesion pathway, but a role for LAMB3 in pancreatic cancer has not been investigated previously 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…The early lethal JEB generalized severe subtype results from absent LM332, while generalized intermediate (JEB-GI) or localized JEB forms associate with variably reduced LM332 amounts. In addition, JEB-related non-blistering conditions with specific tissue manifestations result from dominant haploinsufficiency or from partial loss-of-function that spares the amount and coiled coil domain of the heterotrimer [3,[11][12][13]. JEB-GI can also be due to genetic defects in COL17A1 encoding collagen XVII [14].…”
Section: Introductionmentioning
confidence: 99%